Recent advances in vitrimers: A detailed study on the synthesis, properties and applications of bio-vitrimers - Madduluri, Venkata Rao; Bendi, Anjaneyulu; Chinmay, ,; Maniam, Gaanty Pragas; Rasidi, Roslan; Mohd Hasbi, Ab Rahim (Springer, 2025)
Nowadays, thermoset polymers stand out as notable composites, but the surge in global thermoplastic production has raised concerns due to the non-recyclability of these composites, leading to an increase in landfill waste. In response to these challenges, researchers are investigating innovative approaches to enhance thermosetting materials, focusing on the modification of crosslinking agents responsible for forming a covalently bonded network. Vitrimers offer a promising solution by enabling re-processability while maintaining favourable thermo mechanical properties and solvent resistance. Although many current vitrimers use synthetic polymeric molecules from fossil-based sources, there is a growing interest in bio-based vitrimers. While still in early development, these bio-based alternatives leverage biomass for creating durable polymers, aligning with the goal of establishing a circular economy. This review has been designed to highlight the use of covalently modified networks to produce advanced synthetic and bio-based vitrimer composites with diverse applications, contributing to the development of sustainable materials for the next generation through the use of recyclable resources and renewable feedstocks in polymer network synthesis. This review also explores vitrimers, examining their unique characteristics and addressing current limitations hindering their widespread adoption as recyclable materials with superior performance.